An Application for Studying Tandem Repeats in Orthologous Genes - Lousado, José (2012)
Several authors have being suggesting that the occurrence of amino acids repeats in some genes are implied in human diseases. We aim to investigate if these repetitions, which one can observe in humans, also exist in orthologous genes of several organisms, and how they have evolved along time. However, for this kind of study, it is necessary to use different databases and computation methods that are not integrated in any specific tool. In this paper, we present a bioinformatics application, supported by Web Services, that allows to conduct comparative analysis studies for various organisms, along the evolutionary chain.